Helicobacter pylori Strain 26695 versus J99: Analysis on the Protein Structure and Physicochemical Characteristics - Hamidah Kurniasari; Farah Ayu Noviannisa; Sitisalma Amirah Dzakiyyah; Marsha Zahrani; Muhammad Raihan Habibi; Kartika Afrida Fauzia; Saruuljavkhlan Batsaikhan; Ricky Indra Alfaray (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Helicobacter pylori (HP) has several important virulence factors including Cytotoxin-Associated Gene A (CagA). Studying the protein structure and physicochemical characteristics of CagA from the sequence data are essential to understand their virulence ability. This study compared the protein structure and physicochemical characteristics of CagA western-type HP29965 and J99. Methods: We retrieved the DNA sequences from GenBank, NCBI (HP26695: NC_000915.1; J99: NC_000921.1. Protein modelling from protein sequences using Swiss-Model was visualized using PyMOL. Physicochemical characteristics were obtained using ExPasy ProtParam. Results: CagA HP26695 has Glu-Pro-Ile-Tyr-Ala (EPIYA)-A, EPIYA-B, and EPIYA-C, while CagA J99 lacks EPIYA-A. Both strains have relatively similar tertiary protein structures. CagA J99 has fewer amino acids and molecular weight than CagA 26695. Both strains have negative GRAVY values, a high aliphatic index (>70), and the same estimated half-life. Conclusion: HP J99 only has EPIYA-B and EPIYA-C. Both strains are thermostable and stable. However, J99 is more thermostable and stable than HP26695.